What do we know about decision support systems for landscape and environmental management? A review and expert survey within EU research projects. (December 2017) - Zasada, Ingo; Piorr, Annette; Novo, Paula; Villanueva, Anastasio J.; Valánszki, István
Highlights: The analysis covers 60 EU-funded research projects between 2004 and 2014. In 48% of the cases (N = 29) tools were available online. There is a large thematic and functional heterogeneity among tools. Exchange of knowledge is more important than actual decision support. Stakeholders are often included in tool development, but a structured process is lacking.